The Economics of Tobacco in Lebanon: An Estimation of the Social Costs of Tobacco Consumption. (12th May 2014) - Salti, Nisreen; Chaaban, Jad; Naamani, Nadia
<x xml:space="preserve">Abstract</x> Objectives: Assess the socioeconomic costs of smoking in Lebanon and understand the tobacco market and identify the winners and losers from the Lebanese tobacco trade. Methods: We take a close look at the market for tobacco and related markets to identify the main stakeholders and estimate the direct costs and benefits of tobacco. We also estimate lower bounds for the costs of tobacco, in terms of lost productivity, the cost of medical treatment, lost production due to premature death, and environmental damage. The paucity of data means our cost estimates are conservative lower bounds and we explicitly list the effects that we are unable to include. Results: We identify the main actors in the tobacco trade: the Régie (the state-owned monopoly which regulates the tobacco trade), tobacco farmers, international tobacco companies, local distributors, retailers, consumers, and advertising firms. We identify as proximate actors the Ministries of Finance and Health, employers, and patients of smoking-related illnesses. In 2008, tobacco trade in Lebanon led to a total social cost of $326.7 million (1.1% of GDP). Conclusion: Low price tags on imported cigarettes not only increase smoking prevalence, but they also result in a net economic loss. Lebanese policymakers should consider the overall deficit from tobacco trade and implement the guidelines presented in the Framework Convention on Tobacco Control to at once increase government revenue and reduce government outlays, and save the labor market and the environment substantial costs.